Epidural spinal involvement of Erdheim–Chester disease causing myelopathy. Issue 9 (September 2015) - Hwang, Brian Y.; Liu, Ann; Kern, Jason; Goodwin, C. Rory; Wolinsky, Jean Paul; Desai, Atman
Highlights: Erdheim-Chester Disease (ECD) involvement of the spine is rare. ECD should be considered as a possible cause of myelopathy. Surgery can effectively and safely improve neurological symptoms in ECD patients. Abstract: We present a 25-year-old woman with Erdheim–Chester disease (ECD) presenting with progressive myelopathy from multiple compressive spinal epidural lesions who required cervicothoracic decompression and fusion, and summarize the literature on epidural spinal involvement of ECD. ECD is a rare non-Langerhans histiocytosis affecting multiple organ systems through infiltration and characteristically causing multifocal osteosclerosis. Central nervous system involvement, particularly of the spine, is rare.